Vpliv različnih vadbenih intervencij na kostni sistem pri starejših odraslih - Pavšič, Anja (Šport (Ljubljana), 2024)
Bone is a dynamic tissue that responds to mechanical loading - therefore exercise is important for maintaining or increasing bone mineral density in the elderly. The aim of this umbrella review was to examine the impact of exercise interventions on the skeletal system in older adults. Electronic databases PubMed, Scopus, Web of Science, and Science Direct were scanned for studies, published between 2012 and 2022. Twenty-eight systematic reviews met the inclusion criteria. Evidence for water-based exercise, aerobic exercise, resistance training, impact activities, combined exercise, vibration training, and mind-body exercise was provided. Bone mineral density was measured at the lumbar spine, femoral neck, total hip, trochanter, Ward’s triangle, whole body, tibia, and wrist. Participants were predominantly women. Combined exercise interventions that include resistance training, were found to be the most effective for increasing bone mineral density in older adults. Resistance exercise alone also has a positive impact on the skeletal system. Impact activities are not recommended due to safety concerns. Less effective interventions are water-based, mind-body and aerobic exercise. Vibration training represents an effective alternative for older individuals, who cannot engage in highintensity exercise. In conclusion, any form of exercise can be beneficial, as long as individual’s bone characteristics are considered.
Keywords: active aging; aging; aktivno staranje; bone mineral density; elderly; exercise; mineralna kostna gostota; osteoporosis; osteoporoza; sport; staranje; starejši odrasli; starostnik; šport; vadba